Controllable Droplet Sliding on a Smart Shape‐Memory Slippery Surface. Issue 17 (11th July 2022) - He, Yaoxu; Wang, Zhe; Jiao, Xiaoyu; Song, Yingbin; Meng, Junhui; Cheng, Zhongjun
Abstract: Recently, slippery surfaces with controllable droplet sliding have aroused much attention in both fundamental research and realistic applications. However, for almost all existing surfaces, constant stimuli such as heat, light, magnetic field, etc., are indispensable. Herein, by constructing pit structures on a shape memory polymer and further infusing oil with low surface tension, we report a shape memory slippery surface that can overcome the above imperfection. Based on the shape memory performance, the surface can memorize a diverse pit size as the surface is stretched or recovered. With the variation of pit structure, the sliding performances for both water and organic liquid droplets can be reversibly adjusted between the rolling and pinning states. This work, based on the shape memory effect, reports smart droplet sliding control through regulating the surface microstructure, which not only provides a strategy for droplet sliding control, but also offers some ideas for designing novel intelligent slippery surfaces. Abstract : This work reports a slippery surface prepared by infusing low surface tension oil into pit structured shape memory film. The film can memorize diverse pit structures due to its shape memory effect, which can effectively regulate the infused oil level. Accordingly, the surface and droplet contact model can be adjusted, and switchable sliding/pinning control of liquid droplets can be achieved.